2007
DOI: 10.1016/j.jvs.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of peripheral arterial disease prevalence with special focus on critical limb ischemia and sex differences

Abstract: PAD is common in Sweden, and almost a fifth of all elderly individuals have some stage of this disease. Women are more often afflicted than men. The prevalence of severe ischemia, as a measure of critical limb ischemia, is about 1% the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
210
2
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(258 citation statements)
references
References 40 publications
15
210
2
22
Order By: Relevance
“…TBI was significantly lower in the patients with type 2 diabetes than in the controls. In the control group 13% had a TBI < 0.7 which is similar or slightly higher than earlier reports on PAD frequency as measured by ABI [3,4,21,22].…”
Section: Discussionsupporting
confidence: 81%
“…TBI was significantly lower in the patients with type 2 diabetes than in the controls. In the control group 13% had a TBI < 0.7 which is similar or slightly higher than earlier reports on PAD frequency as measured by ABI [3,4,21,22].…”
Section: Discussionsupporting
confidence: 81%
“…Those studies were conducted in clinical setting but The study by Okello et al and Oyelade et al from Uganda and Nigeria respectively, was conducted among diabetic subjects, where we expect higher prevalence of PAD as compared to the general population. Similarly, PAD in our study is lower than studies from high income countries [21,22], where the prevalence of PAD ranges from 16-18%. This might also be attributed to the differences in the study population.…”
Section: Discussioncontrasting
confidence: 67%
“…Literature reveals no consistent evidence to support differences in the prevalence of PAD between the sexes. Some studies have found a significant difference in the prevalence between males and females [18], while others have not [19]. This study showed positive association between PAD and diabetes.…”
Section: Discussionsupporting
confidence: 43%